2015
DOI: 10.3748/wjg.v21.i42.12003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic management of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is an increasing health problem, representing the second cause of cancer-related mortality worldwide. The major risk factor for HCC is cirrhosis. In developing countries, viral hepatitis represent the major risk factor, whereas in developed countries, the epidemic of obesity, diabetes and nonalcoholic steatohepatitis contribute to the observed increase in HCC incidence. Cirrhotic patients are recommended to undergo HCC surveillance by abdominal ultrasounds at 6-mo intervals. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 257 publications
1
54
1
2
Order By: Relevance
“…Recently, surgical treatments including hepatic resection, liver transplantation, local ablative therapy and transarterial chemoembolization have been the most successful approaches to HCC. Patients with HCC have benefitted from significant improvements in tumor identification and patient survival (3,4). However, the incidence rate of HCC is almost equivalent to its mortality rate in most countries, indicating a lack of early diagnostic methods and effective therapies (5).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, surgical treatments including hepatic resection, liver transplantation, local ablative therapy and transarterial chemoembolization have been the most successful approaches to HCC. Patients with HCC have benefitted from significant improvements in tumor identification and patient survival (3,4). However, the incidence rate of HCC is almost equivalent to its mortality rate in most countries, indicating a lack of early diagnostic methods and effective therapies (5).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the sixth most frequent diagnosed cancer and one of the most common cause of cancer-related death worldwide (1,2). Although the diagnostic and therapeutic techniques of HCC have gradually improved, the morbidity and mortality of HCC continue to show an upward trend (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly prevalent in Asia and sub-Saharan Africa countries (3,4). A progressive increase in HCC-related mortality has been observed in the US and Western Europe (5)(6)(7). Accumulating evidence has revealed that inflammatory-related cytokines participate in the carcinogenesis and progression of HCC (8).…”
Section: Introductionmentioning
confidence: 99%